Structural performance of male-female interlocking panel (M-FiP) connection using Crushed Concrete Waste Aggregate (CCwA) / Mohd Suhelmiey Sobri - Sobri, Mohd Suhelmiey (Institute of Graduate Studies, UiTM, 2017)
This research investigates the performance of male-female interlocking panel joint connection for precast panel applications. The research involved experimental laboratory work testing of twenty four (24) set of male-female interlocking panel (M-FiP) with and without bar as connector mechanism and used cement grout as wet joint binder. The dimensions size of the panel are 900 mm x 500 mm x 75 mm, was prepared using Grade 30 of concrete strength by used Crushed Concrete waste Aggregate (CCwA) size 10 mm and 20 mm as a major component material in concrete mix production. The concrete mix has been designed with water cement ratio of 0.50 and reinforced with B7 rectangular steel fabric type. Due to use recycled aggregate material in production new concrete mix, the fresh and hardened test was conducted to confirm the properties as satisfy according to the standard. The aspect (H/L) and slenderness ratio (H/t) of the panel are 0.55 and 6.67 respectively. In order to investigate the male and female performance the two pilot tests has been conducted in studied the bonding strength and ductility behavior of this joint connection…